Dinamika Partisipasi Politik Digital: Menguji Paradoks Interactivity Cues dan Dominasi Media Richness pada Akun @whatisupindonesia - Nasywa Fauziah Simamora; Detta Rahmawan; Frila Nurfadila (MUKASI: Jurnal Ilmu Komunikasi, 2026)
Instagram has increasingly developed as a platform for the dissemination of social–political information, enabling audiences not only to consume content but also to respond and participate through various forms of interaction. This study aims to examine the effects of interactivity cues and media richness on audience engagement with social–political educational content on the non-commercial informational Instagram account @whatisupindonesia. A quantitative explanatory approach was employed using content analysis of 167 posts, with data analyzed through negative binomial regression. Interactivity cues and media richness were treated as independent variables, while engagement, measured by the number of likes, comments, and shares, served as the dependent variable. The results indicate that media richness has a significant and consistent effect on all engagement indicators, particularly in video-based content. In contrast, interactivity cues show inconsistent effects and tend to be non-significant, or even negative, across several engagement indicators. These findings suggest that within the context of social–political educational content, visual and audiovisual richness plays a more dominant role than explicit interactive prompts in driving audience engagement.